Cyberbullying: Legal Perspectives and Social Implications - Sholikhah, Firda Mar'atus; Purwaningsih, Sri Budi; Rositasari, Dewi (Proceedings of The ICECRS, 2023)
This comprehensive dataset, sourced from Lens.org, examines the landscape of cyberbullying within Cyberlaw, spanning 1954 to 2022. Utilizing a rich keyword set, it delves into scholarly works to explore legal aspects of online harassment, uncovering prolific institutions and active authors driving research, notably the University of Cambridge and David P Farrington. The analysis underscores psychological and sociological dimensions, emphasizing critical themes for Law. It offers insights crucial for legal reforms and social policies, catering to scholars, law enforcement, and policymakers. Highlights: Historical Evolution: Tracing cyberbullying literature from 1954 to 2022. Legal Insights: Emphasizing the role of Cyberlaw and its implications. Societal Impact: Significance for legal reforms and policymaking regarding online harassment. Keywords: Cyberbullying, Cyberlaw, Legal Perspectives, Online Harassment, Social Implications